MODEL ROOT CAUSE ANALYSIS SISTEM INFORMASI PEMERINTAHAN DAERAH (SIPD) DALAM PENGELOLAAN KEUANGAN DAERAH (Studi Empiris Pada Dinas Tenaga Kerja Kabupaten Wonogiri) - Dian Praharaningtyas; Fatchan Achyani; Triyono Triyono (JURNAL ILMIAH EDUNOMIKA, 2024)
Use of the Regional Government Information System (SIPD) as a form of regional government transparency in disclosing information to the public. How SIPD is implemented in regional financial management at the Wonogiri Regency Manpower Service is the focus of this research. The author uses qualitative research with the Root Cause Analysis model "5 Why Analysis", namely asking why five times or repeatedly until finding the root of the problem. The main technique used in data collection is conducting interviews with staff who are SIPD operators by making a list of questions for observation and documentation. The author's conclusion is that not all informants have the same root problems in implementing SIPD. There are 3 main factors that cause less than maximum problems, namely communication constraints, application constraints and human resource constraints.